2006
DOI: 10.1007/s00425-006-0290-4
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity effects on leaf morphology, cell structure, carbon metabolism and mRNA expression of dwarf wheat

Abstract: The use of higher plants as the basis for a biological life support system that regenerates the atmosphere, purifies water, and produces food has been proposed for long duration space missions. The objective of these experiments was to determine what effects microgravity (microg) had on chloroplast development, carbohydrate metabolism and gene expression in developing leaves of Triticum aestivum L. cv. USU Apogee. Gravity naive wheat plants were sampled from a series of seven 21-day experiments conducted durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 47 publications
1
72
1
Order By: Relevance
“…8,9 Our results show that slow clinorotation did not significantly affect the expression of sHSP genes belonging to subfamilies that function in different cellular compartments. These results are consistent with other studies that showed that heat shock proteins were not stimulated in thale cress (Arabidopsis thaliana), 17 wheat (Triticum aest铆vum) 18 and barley (Hordeum vulgare) 19 plants during spaceflight. Based on these studies, it is logical to conclude that simulated microgravity, unlike temperature, does not result in aberrant protein synthesis or folding and, therefore, does not induce changes in sHSP gene expression at the transcriptional level.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…8,9 Our results show that slow clinorotation did not significantly affect the expression of sHSP genes belonging to subfamilies that function in different cellular compartments. These results are consistent with other studies that showed that heat shock proteins were not stimulated in thale cress (Arabidopsis thaliana), 17 wheat (Triticum aest铆vum) 18 and barley (Hordeum vulgare) 19 plants during spaceflight. Based on these studies, it is logical to conclude that simulated microgravity, unlike temperature, does not result in aberrant protein synthesis or folding and, therefore, does not induce changes in sHSP gene expression at the transcriptional level.…”
Section: Discussionsupporting
confidence: 82%
“…5 Cultured cells respond by overexpressing a set of heat shock proteins, including sHSP genes. 5,[17][18][19] sHSP gene expression under microgravity was also confirmed by studies using simulated microgravity. 8,9 Our results show that slow clinorotation did not significantly affect the expression of sHSP genes belonging to subfamilies that function in different cellular compartments.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This potential arises from the confluence of the lifesupport and astrobiology agendas and has kept plant biology firmly within the spaceflight experiment community. Numerous plant experiments have flown in the Space Shuttle and International Space Station payload programs in the last 20 years, and the following citations are only a sampling of this research: Saunders (1968), Bucker (1974), Krikorian et al (1981Krikorian et al ( , 1992, Kordyum et al (1983), Guikema et al (1994), Kuang et al (1996Kuang et al ( , 2000, Levine and Krikorian (1996), Brown et al (1997), Musgrave et al (1997), Porterfield et al (1997), Adamchuk et al (1999), Kiss and Edelmann (1999), Nedukha et al (1999), Sato et al (1999), Gao et al (2000), Levinskikh et al (2000), Levine et al (2001), Kern and Sack (2001), Paul et al (2001Paul et al ( , 2005, Hoson et al (2003), Klymchuk et al (2003), Stutte et al (2006), Salmi and Roux (2008), Johnsson et al (2009), Kiss et al (2009), Ou et al (2009), Visscher et al (2009. Conclusions from plant biology experiments have highlighted biological responses to spaceflight environments and have also illuminated engineering and operational advancements necessary for conducting sound biological experiments in space (reviewed in Halstead and Dutcher, 1987;Dutcher et al, 1994;Ferl et al, 2002;Clement and Slenzka, 2006;…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in space or in earth-based simulations indicate that organisms undergo changes when subjected to environmental factors. These changes include thylakoid membrane structure, mitochondria (Popova 2003;Stutte et al 2006;Klimchuk 2007;Brykov 2011), gene expression (Visscher et al 2009), primary (Popova et al 1989;Stutte et al 2006) and secondary metabolism (Musgrave et al 2005;Nechitailo et al 2008) and so on. Many biological samples cited in the above research were harvested just once after a period of space flight or simulation on a clinostat.…”
Section: Introductionmentioning
confidence: 99%